CAMPUR KODE WAWANCARA ANTARA SUTARMIDJI, M.HUM DAN PENYIAR KOMPAS TV PONTIANAK - Hakim, Uti M Fauzan; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractResearchers in this study took data from YouTube in the form of a video interview between Sutarmidjidan, Kompas TV announcer Pontianak as a data source. Researchers focus on observations in the form of mixed code speech. The problem in this research is the form of code mixing and the factors that cause code mixing between Sutarmidji and Pontianak Kompas TV broadcasters. The purpose of this study is to describe the form of Code Mix and the factors causing code mixing. This research uses descriptive method, with a qualitative form of research, and uses a sociolinguistic approach. The theory used in this research is the theory of language contact, the theory of bilingualism, and the theory of code mixing. Sources of data in this study are Mr. Sutarmidji and broadcaster Kompas TV. Data collection techniques in this study are refer to techniques. The tools used for research are laptop cameras, cellphones, and stationery. The results of the 19 data found are: there are five forms of mixed code, namely, the form of words, phrases, baster, repetition, and clause. Factors that cause code mixing are role factors, willingness to explain and interpret factors and speaker factors and diversity factors.Â Keywords: Sociolinguistics, Code Mix